A Middle Palaeolithic origin of music? : Using cave-bear bone accumulations to assess the Divje Babe I bone 'flute' - D'Errico, Francesco; Villa, Paola; Pinto Llona, Ana C.; Ruiz Idarraga, Rosa
The discovery of a perforated cave-bear femur from the Neanderthal levels at Divje Babe has been interpreted as the oldest musical instrument in Europe. Here we present the current discussion on the 'flute' and its implications for other similar bone finds from early prehistory.